Tartine bread - Robertson, Chad (Chronicle Books, 2010)
The bread at San Francisco's legendary Tartine Bakery was developed by renowned baker Chad Robertson over a decade of working with the finest artisan bakers in the United States and France, followed by another decade baking solo in a small wood-fired oven on the coast of Northern California. The following for this singular bread far exceeds the bakery's daily production. Now, clear instructions and hundreds of step-by-step photos show you how to make this elemental bread. Also included are more than 30 sweet and savory recipes using the day-old bread to make sandwiches, soups, puddings, French toast and kale Caesar.--From publisher description.